Work-Life Quality and Organizational Culture as Foundations for Professional Well-Being and Life Satisfaction in Contemporary Work Environments - Eddine, Belouadah Ahmed Seif; Mendonca, Cipriano Nunes (Metromedia, 2025)
This study investigates the relationship between work-life quality and life satisfaction, exploring the multifarious ways in which organizational culture, management practices, and workplace structures shape the totality of individual well-being. Through a rigorous qualitative literature review and thematic synthesis approach, the study draws upon empirical and theoretical perspectives spanning diverse occupational contexts, emphasizing the salience of psychological safety, autonomy, flexibility, and recognition. The findings affirm that life satisfaction is integrally linked to professional experiences, with effective work-life policies, supportive leadership, and equitable environments fostering satisfaction both within and beyond the workplace. Conversely, organizational rigidity, lack of support, and unchecked digital encroachment undermine psychological health and erode meaning. The study underscores the vital role of emotional intelligence, social support structures, and gender equity initiatives in creating climates conducive to holistic thriving. Practical implications include recommendations for policy innovation, leadership development, and the strategic realignment of cultures to endorse meaningful, sustainable, and dignified work. This research provides nuanced insights and actionable pathways for organizations, policymakers, and scholars committed to advancing both occupational well-being and broader societal prosperity.